the problem is:
(x^2 - y^2)^2 / x^2 + 2xy + y2
the answer is supposed to be:
x^2 - 2xy +y2
i get to x^2 - 2x^2y^2 + y^2 / 2xy
what am i missing?
thanks
$\displaystyle
{(x^2-y^2) =(x+y)(x-y)}
$
$\displaystyle
{(x+y)^2 = (x^2 +2xy +y^2) }
$
$\displaystyle
{(x-y)^2 = (x^2-2xy +y^2)}
$
$\displaystyle
(x^2-y^2)^2 =(x+y)^2(x-y)^2...........\text{Use in numerator}
$
$\displaystyle
(x^2 +2xy +y^2)= (x+y)^2 ...........\text{Use in denominator}
$
$\displaystyle
(x^2-2xy +y^2)=(x-y)^2 ...........\text{use in the last step}
$